Understanding a continuous inland aeolian deposition: a closer look into a chronological and sedimentary record of the north-eastern European Sand Belt - Kalińska, Edyta (Bulletin of Geography. Physical Geography Series, 2019)
A belt of inland aeolian sand sediments termed the European Sand Belt (ESB) runs throughout Europe, and its western part has gained greater attention, while attention to the eastern part has been limited. Whereas clear aeolian–paleosol sequences that reflect colder–-armer phases are known from its western part, such alternation is practically undetectable in the eastern part. This study combines the available chronological and sedimentary data from the north-eastern part of the ESB, with a special focus on the Baltic State region. Here, aeolian deposition took place between 15.9±1.0 ka and 8.5±0.5 ka, almost instantly following a deglaciation and drainage of paleolakes, and thereafter practically without longer-term stability. Lack of paleosols is likely due to the prevalence of pioneer vegetation, reflecting dry and cold climate conditions, and thus giving limited opportunity for soil development.